2017
DOI: 10.1002/zoo.21361
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intrinsic enrichment on captive felids

Abstract: Environmental enrichment is a well-known technique, which has been used to enhance the welfare of captive animals. The aim of this study is to investigate how three different forms of intrinsic enrichment, namely, a hay ball without scent, a hay ball with catnip, and a hay ball with cinnamon, influenced the behavior of six cheetah and two Sumatran tigers at Fota Wildlife Park, Ireland. Enrichment-directed behaviors, as well as pacing, locomotion, inactive, and exploratory behaviors were investigated. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…Nonetheless, it has been demonstrated that indicators of impoverished captive tiger welfare were sensitive to habitat size [40,41], broadly supporting the conclusions of Clubb and Mason [35]. However, tiger welfare also appeared to be sensitive to habitat quality [40,42], as well as enrichment and feeding regimes [32,40,[43][44][45][46][47][48], suggesting that much can be achieved to augment captive tiger welfare by understanding their psychological needs and manipulating their habitats and management accordingly [13,23,28]. In 2018, an assessment of the psychological priorities of Amur tigers was carried out at the Korkeasaari Zoo in Helsinki, Finland.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Nonetheless, it has been demonstrated that indicators of impoverished captive tiger welfare were sensitive to habitat size [40,41], broadly supporting the conclusions of Clubb and Mason [35]. However, tiger welfare also appeared to be sensitive to habitat quality [40,42], as well as enrichment and feeding regimes [32,40,[43][44][45][46][47][48], suggesting that much can be achieved to augment captive tiger welfare by understanding their psychological needs and manipulating their habitats and management accordingly [13,23,28]. In 2018, an assessment of the psychological priorities of Amur tigers was carried out at the Korkeasaari Zoo in Helsinki, Finland.…”
Section: Introductionmentioning
confidence: 79%
“…Evidence from multiple sources appear to show that the habitat quality of captive carnivores can be augmented without increasing captive habitat size [33]. Within the constraints of the existing captive habitats, opportunities to investigate feeding devices throughout the day significantly reduced the incidence of pacing amongst captive tigers [47], as did bungee-carcass feeding [48], olfactory enrichment [44] and the provision of live fish and bones [32]. Furthermore, it has been shown that both increased habitat complexity and quality appeared to diminish pacing across a variety of tiger subspecies [40].…”
Section: The Impact Of a Wide-ranging Lifestylementioning
confidence: 99%
“…Uccheddu and colleagues [43], for example, exposed domestic dogs to a variety of essentials oils, and found that some scents increased frequencies of behavioural indicators of relaxation while others decreased behavioural indicators of stress such as pacing and over-grooming. Similarly, a study on cheetahs and Sumatran tigers (Panthera tigris sumatrae) found that stereotypic pacing behaviour was significantly decreased in the presence of a hay ball with cinnamon [44]. This is consistent with the work conducted by Higham and colleagues [45] showing that, among olive baboons (Papio anubis), both short-term (i.e., day-to-day) and long-term variation in rates of self-directed variation does not reflect changes in FGCs.…”
Section: Discussionmentioning
confidence: 94%
“…The provision of enrichment techniques is a mean to reduce levels of stereotypy and inactivity in captive felines Powell, 1995;Skibiel, Trevino, & Naugher, 2007). Provision of cardboard box and toys, hiding refuges, elevated platforms, and olfactory enrichment are few recommended enrichment techniques to ensure optimal welfare (Bashaw et al, 2003;Damasceno et al, 2017;Jenny & Schmid, 2002;Markowitz & LaForse, 1987;McPhee, 2002;Mellen & Shepherdson, 1997;Mohapatra et al, 2010). Such techniques aid to encourage feeding, exploration, and interaction by eliciting species-specific behaviors.…”
Section: Guptamentioning
confidence: 99%